An allometric approach to quantify the extinction vulnerability of birds and mammals. Issue 3 (March 2016) - Hilbers, J. P.; Schipper, A. M.; Hendriks, A. J.; Verones, F.; Pereira, H. M.; Huijbregts, M. A. J.
Abstract: Methods to quantify the vulnerability of species to extinction are typically limited by the availability of species‐specific input data pertaining to life‐history characteristics and population dynamics. This lack of data hampers global biodiversity assessments and conservation planning. Here, we developed a new framework that systematically quantifies extinction risk based on allometric relationships between various wildlife demographic parameters and body size. These allometric relationships have a solid theoretical and ecological foundation. Extinction risk indicators included are (1) the probability of extinction, (2) the mean time to extinction, and (3) the critical patch size. We applied our framework to assess the global extinction vulnerability of terrestrial carnivorous and non‐carnivorous birds and mammals. Irrespective of the indicator used, large‐bodied species were found to be more vulnerable to extinction than their smaller counterparts. The patterns with body size were confirmed for all species groups by a comparison with IUCN data on the proportion of extant threatened species: the models correctly predicted a multimodal distribution with body size for carnivorous birds and a monotonic distribution for mammals and non‐carnivorous birds. Carnivorous mammals were found to have higher extinction risks than non‐carnivores, while birds were more prone to extinction than mammals. These results are explained by the allometric relationships, predicting the vulnerable species groups to have lower intrinsic population growth rates, smaller population sizes, lower carrying capacities, or larger dispersal distances, which, in turn, increase the importance of losses due to environmental stochastic effects and dispersal activities. Our study is the first to integrate population viability analysis and allometry into a novel, process‐based framework that is able to quantify extinction risk of a large number of species without requiring data‐intensive, species‐specific information. The framework facilitates the estimation of extinction vulnerabilities of data‐deficient species. It may be applied to forecast extinction vulnerability in response to a changing environment, by incorporating quantitative relationships between wildlife demographic parameters and environmental drivers like habitat alteration, climate change, or hunting.